Friedreich's ataxia-associated childhood hypertrophic cardiomyopathy: a national cohort study. Issue 5 (5th October 2021) - Norrish, Gabrielle; Rance, Thomas; Montanes, Elena; Field, Ella; Brown, Elspeth; Bhole, Vinay; Stuart, Graham; Uzun, Orhan; McLeod, Karen A; Ilina, Maria; Adwani, Satish; Daubeney, Piers; et al.
Abstract : Objective: Hypertrophic cardiomyopathy (HCM) is an important predictor of long-term outcomes in Friedreich's ataxia (FA), but the clinical spectrum and survival in childhood is poorly described. This study aimed to describe the clinical characteristics of children with FA-HCM. Design and setting: Retrospective, longitudinal cohort study of children with FA-HCM from the UK. Patients: 78 children (<18 years) with FA-HCM diagnosed over four decades. Intervention: Anonymised retrospective demographic and clinical data were collected from baseline evaluation and follow-up. Main outcome measures: The primary study end-point was all-cause mortality (sudden cardiac death, atrial arrhythmia-related death, heart failure-related death, non-cardiac death) or cardiac transplantation. Results: The mean age at diagnosis of FA-HCM was 10.9 (±3.1) years. Diagnosis was within 1 year of cardiac referral in 34 (65.0%) patients, but preceded the diagnosis of FA in 4 (5.3%). At baseline, 65 (90.3%) had concentric left ventricular hypertrophy and 6 (12.5%) had systolic impairment. Over a median follow-up of 5.1 years (IQR 2.4–7.3), 8 (10.5%) had documented supraventricular arrhythmias and 8 (10.5%) died (atrial arrhythmia-related n=2; heart failure-related n=1; non-cardiac n=2; or unknown cause n=3), but there were no sudden cardiac deaths. Freedom from death or transplantation at 10 years was 80.8% (95% CI 62.5 to 90.8). Conclusions: This is the largest cohort of childhood FA-HCM reported to date and describes a high prevalence of atrial arrhythmias and impaired systolic function in childhood, suggesting early progression to end-stage disease. Overall mortality is similar to that reported in non-syndromic childhood HCM, but no patients died suddenly. Abstract : In the largest cohort of children with Hypertrophic Cardiomyopathy associated with Friedrich's Ataxia presented to date a surprisingly high prevalence of atrial arrhythmias are described, and a reminder of the need for serial cardiac screening in these children is reinforced.